Where John Barleycorn Still Holds Forth in Splendor: A Case Study of Prohibition in Wisconsin - Wachter, Jonathan R. (My University, 2007)
This paper takes a look at Wisconsin Prohibition by focusing on a small town in southwest Wisconsin called Prairie du Chien. This paper starts by giving a background on early taverns in Prairie du Chien and why people liked going to taverns. The paper then goes into why Prairie du Chien and in a wider scope Wisconsin did not like Prohibition. The paper goes over how German ethnicity, religion, geography, economics, politics, and law enforcement all took a part in the demise of Prohibition in Prairie du Chien and Wisconsin.
Keywords: Prohibition--Wisconsin--Prairie du Chien.; Prohibition--Social aspects--Case studies.; Prairie du Chien (Wis.)--Social life and customs--20th century.; Prohibition--Wisconsin--Public opinion.